2015
DOI: 10.1089/jwh.2014.4948
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Rectal Gonorrhea and Chlamydia Infection in Women Attending a Sexually Transmitted Disease Clinic

Abstract: Background: Testing women for urogenital Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) is common in sexually transmitted disease (STD) clinics. However, women may not be routinely tested for rectal GC/CT. This may lead to missed infections in women reporting anal intercourse (AI). Methods: This was a retrospective review of all women who underwent rectal GC/CT testing from August 2012 to June 2013 at an STD clinic in Columbus, Ohio. All women who reported AI in the last year had a rectal swab colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Chlamydia trachomatis antigens have been detected in enteroendocrine cells and macrophages of the small bowel in patients with severe irritable bowel syndrome (24), although the association of chlamydial infection in the GI tract with intestinal inflammatory diseases remains unclear (25,26). The high prevalence of C. trachomatis infection in the GI tract (21,27,28) has prompted screening for chlamydial infection in both cervicovaginal and rectal swabs from both sexually active men and women (29,30). Large-scale screenings of both cervicovaginal and rectal swabs not only will provide information for treatment and follow-up but may also aid in our understanding of the exact relationships between the vaginal and rectal C. trachomatis organisms in humans.…”
mentioning
confidence: 99%
“…Chlamydia trachomatis antigens have been detected in enteroendocrine cells and macrophages of the small bowel in patients with severe irritable bowel syndrome (24), although the association of chlamydial infection in the GI tract with intestinal inflammatory diseases remains unclear (25,26). The high prevalence of C. trachomatis infection in the GI tract (21,27,28) has prompted screening for chlamydial infection in both cervicovaginal and rectal swabs from both sexually active men and women (29,30). Large-scale screenings of both cervicovaginal and rectal swabs not only will provide information for treatment and follow-up but may also aid in our understanding of the exact relationships between the vaginal and rectal C. trachomatis organisms in humans.…”
mentioning
confidence: 99%
“…This is especially true given two recent screening studies that reported higher rates of extragenital STIs among the youngest female cohorts in their studies (under 19 and under 26, respectively) [6, 7]. However, the low rates of STI consideration in this population are not surprising given previous literature demonstrating that even among female adolescents with typical genitourinary symptoms of STI presenting to a single PED, 20% did not have a sexual history documented [10].…”
Section: Discussionmentioning
confidence: 82%
“…STIs often present with genitourinary symptoms; however, most, including HIV, GC and CT, can also present with oropharyngeal or anorectal manifestations [5]. Although the prevalence of oropharyngeal and anorectal STIs or STI manifestations among adolescents is unknown, two recent screening studies of adolescents and adults found an association between younger age and extragenital GC and/or CT in females [6, 7], which suggests that adolescents may be at heightened risk. Further, with urogenital screening only, which is the most common practice, there is evidence that a large number of STIs are missed and the CDC recommends testing with NAAT at the anatomic site where symptoms occur [5, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Si bien no se encontraron diferencias entre trabajadoras sexuales portadoras y no portadoras para aquellas conductas que puedan suponer factores de riesgo (uso de alcohol y drogas, uso de preservativo), es posible que dicha diferencia esté dada por características de sus clientes, en términos de la portación por parte de estos C. trachomatis u otros patógenos de transmisión sexual, o de sus hábitos. Estudios actuales avalan esta teoría, ya que se ha documentado una mayor prevalencia de ITS en mujeres que han declarado tener sexo con individuos que consumen drogas, con individuos que pagan por sexo, con compañeros sexuales desconocidos o que han tenido sexo bajo los efectos de las drogas o el alcohol 12 . Todas las situaciones descritas son más comunes en las trabajadoras sexuales que en las mujeres que no realizan esta actividad, lo que pone a este grupo en una situación de mayor riesgo.…”
Section: Discussionunclassified